Pradigma Pendidikan Dalam Al-Qur‟an: Menganalisis Profil Guru Dalam Perspektif Al-Qur‟an - Azahra, ‎ Fatma; Charles, Charles (Institut Teknologi Pendidikan Indonesia, 2022)
Educators as the most important component in the world of education become figures in theirenvironment in delivering their students a brighter future. Educators as the spearhead insuppressing ignorance and immorality, of course, must have Qur'anic characteristics persuasively and constructively. If in the Al-Qur'an at least four classifications of educators are mentioned, basically they have